The Prevalence of Refractive Errors in Students from Basrah, Iraq - Aymen Majeed Fadil Dirawi (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2023)
Introduction: Visual impairment affects students' routine in school time and day-to-day activities. This study aimed to describe the prevalence of refractive errors in students from Basrah, Iraq. Methods: This research was an observational study with a cross-sectional design. A total of 105 students participated in this study. The inclusion criteria for the participant were pediatric patients aged 6-15 years old who attended the private ophthalmological clinic in Basrah. The children were evaluated for refractive error by ophthalmologists using Snellen charts, auto refractometer, retinoscopy, and slit-lamp biomicroscopy. Obtained data were analyzed using the SPSS program version 24.0. Results: The prevalence of refractive error was found to be 37/105 (35.24%). The difference in the refractive error types between the students was found to be highly significant (p= 0.01). The majority of the students, 18(48.65%), reported myopia, followed by astigmatism 12(32.43%), and hypermetropia 7(18.92%). The difference in the proportion of risk factors such as watching TV, using a mobile, using a computer, playing video games, and having a family history of refractive error were found to be statistically significant (p-value ≤0.05). Conclusion: The prevalence of refractive errors is high in school students. The common refractive error was found to be myopia.